Mining cultural landscape as potential heritage to Malaysia? Insight lens: The perspective of Kinta valley Residents / Suriati Ahmad ... [et al.] - Ahmad, Suriati; Jones, David S.; Zakaria, Ahmad Zamil; Mohd Hussain, Nur Huzeima (Universiti Teknologi MARA, Perak, 2021)
The cultural construction through landscape condense with values that further links to sense of place - genius loci and identity. Identity on the other hand is essential to 'sense of place' and creates meaning for people who experience the everyday landscape. Having regard to place, identity and heritage, this paper focusses upon the resident's perspective in perceiving the merit embedded within the ruin image of the Kinta Valley. Maintaining the qualitative inquiry, the findings of this investigation will enrich the cultural heritage of the place having regard to integrity and authenticity that further defined and characterized Kinta Valley's regional post-industrial mining landscape today.